Six Minute Walk Test as a Monitoring tool in Chronic Obstructive Pulmonary Disease on Pulmonary Rehabilitation - Prakash, Vignan Kumar Gali; Gogineni, Sujath; Kumar, Rajesh; Shaik, Mahaboob V (Journal of Advances in Internal Medicine, 2013)
Background and Aims- The six minute walk test is widely used as an outcome measure in pulmonary rehabilitation programs. The objective of this study is to report the magnitude of change in the six minute walk test with test repetition in patients with chronic obstructive pulmonary disease on pulmonary rehabilitation program. Methods: A prospective study of 51 patients with moderate to very severe COPD was carried out. Clinical examination, spirometry, six minute walk distance were done. All were advised regular follow up visits at three, six and twelve months. Results: Four (8%) very severe cases completed all visits and one in those showed improvement in Forced Expiratory Volume in 1 second by 6% and six minute walk distance by 71 metres. Seven (31.37%) severe cases completed all visits; showed improvement in Forced Expiratory Volume in 1 second by 2.5%; the distance walked was a mean 381.5 metres and this was 2.5 % improvement over base line walking distance. Six (11%) moderately severe cases completed the study; the mean distance walked at the end of the study was 451 metres, which is an improvement of 53% and the mean change in Forced expiratory volume in 1 second was <2%. Totally, the mean of modified Burden of Lung disease Dyspnoea scale was 1.7 (baseline) and 4 (after the test). Conclusions: These findings support the recommendation of practice six minute walk test at baseline assessment in order to provide an accurate measure of the effects of rehabilitation on six minute walk distance. DOI: http://dx.doi.org/10.3126/jaim.v2i2.8774 Journal of Advances in Internal Medicine 2013;02(02):35-41.